Adherence to the Mediterranean Diet in Pregnancy and Its Benefits on Maternal-Fetal Health: A Systematic Review of the Literature - Zaragoza-Martí, Ana; Ruiz-Ródenas, Nuria; Herranz-Chofre, Irene; Sánchez-SanSegundo, Miriam; Serrano Delgado, Verónica de la Cruz; Hurtado-Sánchez, Jose Antonio (Frontiers in Nutrition, 2022)
Introduction Pregnancy is a transcendent period for the mother and the fetus, characterized by an increase on energy requirements. Mediterranean diet (MD) is considered a healthy eating pattern that can provide the nutritional requirements of pregnancy and protect from the development of obstetric pathologies. Objective To know the relationship between adherence to the MD and its maternal-fetal benefits. Methodology A systematic review was conducted by identifying articles in the PubMed and Cochrane databases. The publication date of the studies was between 2010 and 2020, and the inclusion criteria established were that the articles were written in English and Spanish and were accessible in full text. Studies concerning assisted reproduction, gene modulation, conference abstracts, systematic reviews, and pilot studies were excluded. Results Finally, a total of 14 studies were included in the review. The association between the MD and the reduction of some pathologies of pregnancy, such as gestational diabetes, overweight or obesity, sleep quality, complications of childbirth, urinary tract infections (UTIs), and alterations in fetal growth was demonstrated, as well as perinatal problems, including birth weight, prematurity, gastroschisis, and other childhood problems. Conclusion The MD is an optimal diet to consume during pregnancy.